Animal Recognition Application Based on Food Type Using Android Based Augmented Reality - Dona Ardiansyah; Ade Eviyanti; Arif Senja Fitrani (Universitas Muhammadiyah Sidoarjo, 2022)
Augmented reality (AR) is a technology with the concept of combining the dimensions of the real world with the dimensions of the virtual world that is displayed in real time. Augmented reality is not like virtual reality which replaces the real world augmented reality only adds and complete this ,this is done by drawing there-dimensional object on the marker, which is a pattern that is unique and can be recognized by its application this method often called the single marker and 3D method tracking objects smartphones allowed the development of augmented reality applications easily inexpensively and can be accessed by many users augmented reality can be utilized in various fields for example for the means of developing children’s education by playing and learning using augmented reality such as using a smartphone as learning medium by using augmented reality android based reality with a marker object to bring up 3d animal objects as a medium for learning and introducing animals bases on the type of food.